Revitalizing Sustainability in Mathematics Education: The Case of the New Norwegian Curriculum - Solomon A. Tesfamicael; Ole Enge (MDPI AG, 2024)
This paper aims to discuss the revitalization of education for sustainable development (ESD) in mathematics education, particularly in relation to mathematics curricula for grades 1-10, using the example of the new Norwegian curriculum, LK20, which came into effect at the beginning of the 2020 school year. Several studies in the past two decades have identified disengagement of sustainability learning (SL) within mathematics education and called for a change in the philosophy of mathematics education to integrate sustainability into the teaching and learning of mathematics. Using the qualitative content analysis method, we examined three types of documents: the core curriculum, the mathematics curriculum, and one Norwegian mathematics textbook series called Matemagisk. We find that sustainable development (SD) is one of the interdisciplinary issues addressed in LK20. Even though the mathematics curriculum does not explicitly incorporate terms such as 'sustainability' or 'sustainable development', indicating that mathematics and sustainability are unconnected, its six core elements-exploration and problem-solving, modeling and applications, reasoning and argumentation, representation and communication, abstraction and generalization, and mathematical fields of knowledge-provide opportunities for integrating sustainability learning (SL). On the other hand, looking at one of the mathematics textbook series, Matemagisk, for grades 4, 7, and 10, it appears that tasks that use sustainability contexts were included implicitly or explicitly, indicating another opportunity to facilitate sustainable learning. By including sustainability contexts in tasks and mathematical activities, it is possible to boost the process of embedding ESD in mathematics education without compromising content.